The Effect Of The (K.W.L.H) Strategy In Developing Generative Thinking Skills Among Fifth-Grade Students In The First Cycle Schools Of The Basic Education Stage In Damascus Governorate (Damascus University Journal of educational and Psychologyical sciences, 2024)
The research aimed to measure the impact of the (K.W.L.H) strategy in developing generative thinking skills among fifth-grade students in Quneitra, The researcher followed the experimental approach, and a study plan for the first unit of science was prepared according to the (K.W.L.H) strategy and the test of generative thinking skills, It was applied to the research sample, which consisted of (38) male and female students, a control group, and (38) male and female students, an experimental group, The research reached the following results:• There is a statistically significant difference between the mean scores of the students of the experimental group that learned according to the (K.W.L.H) strategy in the pre and post applications of the generative thinking skills test.• There is a statistically significant difference between the mean scores of the control and experimental group students in the post application on the generative thinking skills test in favor of the experimental group that was taught according to the (K.W.L.H) strategy.• A set of proposals has been developed in the light of the previous results.Suggestions: In the light of the previous results, the researcher presents the following proposals:1-Preparing training courses for teachers and students of faculties of education and a "teacher's guide" to facilitate the use of the (K.W.L.H) strategy in the educational field.2- Conducting a study on developing the competencies of teacher in the field of employing the (K.W.L.H) strategy.A study on the impact of the (K.W.L.H) strategy on developing the thinking of learners at different stages.
Keywords: (K.W.L.H) Strategy; Generative Thinking Skills